2022
DOI: 10.1073/pnas.2116271119
|View full text |Cite
|
Sign up to set email alerts
|

Lung-selective mRNA delivery of synthetic lipid nanoparticles for the treatment of pulmonary lymphangioleiomyomatosis

Abstract: Safe and efficacious systemic delivery of messenger RNA (mRNA) to specific organs and cells in vivo remains the major challenge in the development of mRNA-based therapeutics. Targeting of systemically administered lipid nanoparticles (LNPs) coformulated with mRNA has largely been confined to the liver and spleen. Using a library screening approach, we identified that N-series LNPs (containing an amide bond in the tail) are capable of selectively delivering mRNA to the mouse lung, in contrast to our previous di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
175
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(231 citation statements)
references
References 52 publications
2
175
1
2
Order By: Relevance
“…Plasma proteins are known to opsonize foreign nanomaterials in the blood, forming so-called “biomolecular coronas”, which leads to recognition and inactivation of nanomaterials by the immune system. The formation of biomolecular coronas on Doxil in vivo in human systemic circulation has been previously described . Recently, the composition of biomolecular coronas was also found to regulate fate and/or utility of LNPs. , In our previous studies, we found that the enrichment of immunoglobulins and complement proteins in biomolecular coronas is correlated with donor-specific nanoparticle association with human blood immune cells . The studies herein demonstrate that anti-PEG antibodies are probably one of the key immunoglobulins that drive the donor-dependent immune cell association of PEG-containing nanoparticles in human blood.…”
Section: Resultsmentioning
confidence: 91%
“…Plasma proteins are known to opsonize foreign nanomaterials in the blood, forming so-called “biomolecular coronas”, which leads to recognition and inactivation of nanomaterials by the immune system. The formation of biomolecular coronas on Doxil in vivo in human systemic circulation has been previously described . Recently, the composition of biomolecular coronas was also found to regulate fate and/or utility of LNPs. , In our previous studies, we found that the enrichment of immunoglobulins and complement proteins in biomolecular coronas is correlated with donor-specific nanoparticle association with human blood immune cells . The studies herein demonstrate that anti-PEG antibodies are probably one of the key immunoglobulins that drive the donor-dependent immune cell association of PEG-containing nanoparticles in human blood.…”
Section: Resultsmentioning
confidence: 91%
“…However, significant luciferase fluorescence was only observed in the whole liver ( Figures 3A-C ), signifying the liver-targeted protein expression of mRNA-AX4-LNP. It is well known that the liver-targeting LNP acquired of ApoE in the serum results in uptake of lipoproteins by liver hepatocytes through receptor-mediated endocytosis by low-density lipoprotein receptor (LDL-R) [10, 14] . To explore whether the endogenous ApoE affects the protein expression level of mRNA-AX4-LNP in different organs, a ApoE knockout (ApoE - / - ) mouse model was employed.…”
Section: Resultsmentioning
confidence: 99%
“…22 Recently, the composition of biomolecular coronas was also found to regulate fate and/or utility of LNPs. 28,29 In our previous studies we found that the enrichment of immunoglobulins and complement proteins in biomolecular coronas is correlated with donor-specific nanoparticle association with human blood immune cells. 19 The studies herein demonstrate that anti-PEG antibodies are key immunoglobulins that drive the donor-dependent immune cell association of PEG-containing nanoparticles in human blood.…”
mentioning
confidence: 95%